Further investigation of Melocalamus (Poaceae, Bambusoideae) in China based on Skmer analysis and morphology - Yu-Jin Chen; Mei Chen; Meng-Yuan Zhou; Zu-Chang Xu; Yu-Xiao Zhang; Jing-Xia Liu; De-Zhu Li (PhytoKeys, 2025)
Melocalamus is a genus of paleotropical woody bamboos distributed in Southeast Asia, characterised by its complex taxonomic history. Currently, the taxonomic status of several species within Melocalamus remains unresolved, primarily due to incompleteness of vegetative specimens for identification, coupled with scarcity of floral and fruit specimens and phylogenetic discordance. To address these issues, we developed a genome skimming dataset with multiple samples per species of Melocalamus through the Skmer approach. Genetic and morphological evidence supports the transfer of M. elevatissimus to Cephalostachyum, with a new combination, C. elevatissimum. Based on a comprehensive evaluation that integrates morphological characters, molecular data and geographic distribution, we propose treating M. utilis as a synonym of M. orenudus and provide the description of its inflorescence and an epitype of it for the first time. Our results further indicate that M. ningmingensis is a synonym of Neomicrocalamus prainii. We also described a new species, M. guangxiensis from Ningming, Guangxi, based on morphological and molecular evidence. Our results demonstrate both the efficiency and reliability of the Skmer approach in species discrimination while emphasising the importance of integrating morphological characters with genomic data for accurate species classification in Melocalamus.